2019
DOI: 10.1002/jcp.28525
|View full text |Cite
|
Sign up to set email alerts
|

miR‐548c‐5p inhibits colorectal cancer cell proliferation by targeting PGK1

Abstract: Accumulating studies have implicated that microRNAs (miRNAs) are involved in the pathogenesis of colorectal cancer (CRC). However, the role of miR‐548c‐5p, a novel identified miRNA in malignancies, in colorectal carcinogenesis remains largely unknown. The present study is aimed to investigate the effect and molecular mechanism of miR‐548c‐5p in CRC by a sequence of cellular experiments. miR‐548c‐5p was significantly downregulated, whereas phosphoglycerate kinase 1 (PGK1), a key enzyme for glycolysis, was obvio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Because of this, scientists are working hard to explore PGK1 inhibitors. Very recently, miRNA-450b-3p, miR-548c-5p, miRNA-215-5p, and miR-6869-5p have been reported to directly target PGK1 3 -UTR and repress PGK1 expression (Chen et al, 2019(Chen et al, , 2020Ge et al, 2019;Wang et al, 2020). However, it remains unknown whether these miRNAs regulate the Warburg effect and whether the Warburg effect is responsible for cancer cell growth by these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, scientists are working hard to explore PGK1 inhibitors. Very recently, miRNA-450b-3p, miR-548c-5p, miRNA-215-5p, and miR-6869-5p have been reported to directly target PGK1 3 -UTR and repress PGK1 expression (Chen et al, 2019(Chen et al, , 2020Ge et al, 2019;Wang et al, 2020). However, it remains unknown whether these miRNAs regulate the Warburg effect and whether the Warburg effect is responsible for cancer cell growth by these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that miRNAs are involved in cancer cell proliferation, invasion and metastasis. Recently, miRNA-450b-3p, miRNA-548c-5p, miRNA-215-5p, and miRNA-6869-5p have been shown to directly target PGK1 3 -UTR and inhibit PGK1 expression (Chen et al, 2019(Chen et al, , 2020Ge et al, 2019;Wang et al, 2020). These miRNAs can regulate cancer cell proliferation, migration and/or invasion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bone marrow MSC‒derived miR‐1180 accelerates ovarian cancer cell growth and glycolysis through the SFRP1/Wnt pathway 48 . MiR‐548c‐5p represses cell proliferation via targeting PGK1 in colorectal cancer 49 . Accumulating evidence has demonstrated that lncRNAs can function as ceRNAs by competitively binding to miRNAs in various cancers 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to upregulated miRNAs, downregulated miRNAs such as miR-144 , miR-548c-5p , and miR-198 also play important roles in tumorigenesis. MiR-144 has been reported to target GSPT1 to inhibit the metastasis of CRC (Xiao et al, 2015), and miR-548c-5p has been found to act as a tumor suppressor in CRC by targeting PGK1 (Ge et al, 2019). The above results indicate that dysregulated miRNA expression has been observed in CRC and that the abnormal expression of specific miRNAs is associated with metastasis and prognosis in CRC.…”
Section: Discussionmentioning
confidence: 99%